Real-world racial disparities in EGFR testing and third-generation EGFR TKI use among U.S. patients with stage IV NSCLC. Issue 28 (1st October 2022) - Sacchi, Elizabeth; Li, You; Miller, Vincent A.; Curtis, Melissa D.; Ali, Siraj Mahamed
Abstract : 124 Background: Biomarker testing for EGFR mutations (EGFRm) is recommended for all newly diagnosed patients with metastatic NSCLC. Third-generation EGFR TKIs are the recommended standard-of-care therapy for patients with EGFRm+ NSCLC regardless of race, although EGFRm occur more frequently in Asian patients (Table). We investigated the association between race, EGFR testing and receipt of subsequent first-line (1L) treatment with the third-generation EGFR TKI, osimertinib. Methods: This retrospective, observational study used the nationwide Flatiron Health EHR-derived de-identified database. Adults with an initial diagnosis of stage IV NSCLC who initiated systemic 1L therapy between Apr 2018 (osimertinib approval) and Feb 2022 (data cutoff date) were eligible. Two cohorts were defined: those eligible for EGFR testing, and those EGFRm+ patients eligible for 1L osimertinib. Multivariable logistic regression was used to investigate odds of 1) EGFR testing, and 2) 1L osimertinib use, by race. Random-effects logistic regression was used as a sensitivity analysis to evaluate the impact of inter-practice variation on each outcome. Confidence intervals (CI) were calculated at 95%. Results: 9, 505 patients were eligible for EGFR testing. After adjustment, Asian patients were nearly twice as likely to be tested (adjusted odds ratio [aOR]: 1.93, CI: 1.33 – 2.89, p = 0.0001), while Black patients were 25% less likely to receive testing (aOR: 0.75, CI: 0.62 – 0.90, p = 0.002), both relative to White patients. Including a random factor of practice attenuated the effect of race for Asian patients (aOR: 1.74, CI: 1.15 – 2.64, p = 0.0009) as well as Black patients (aOR: 0.8, CI: 0.65-0.97, p = 0.021). Of these patients, 1, 247 were confirmed EGFRm+ and were thus eligible for 1L osimertinib. Asian patients were marginally more likely to receive 1L osimertinib, even after adjustment ( aOR : 1.51, CI : 0.958 – 2.43, p =.082). The inclusion of a random factor of practice diminished the marginal effect of race ( aOR : 1.46, CI : 0.90 – 2.36, p = 0.1). Conclusions: Retrospective analyses using real-world data revealed differences across races in EGFR testing among patients with stage IV NSCLC, suggesting disparities in quality of care. Racial disparities were also observed in 1L osimertinib use among patients with EGFRm+. Sensitivity analyses suggest that these disparities may partially be attributed to differences in care between practices. Future studies are warranted to further characterize this unexpected race-based difference in biomarker testing and treatment initiation. This work highlights the need for investigations of racial disparities in access to both biomarker testing and effective treatment options across precision oncology.Ethnicity/Race White Black Asian Hispanic or Latino Other Unknown EGFRm+ among those tested (%) by race 14 14 54 29 17 18